Investigating land use dynamics in emerging cities: the case of downtown neighbourhood in Doha - Hatem Ibrahim (18112237) (2019)
The study of land use dynamics in emerging cities will inform sustainable development in the future. Doha has witnessed urban transition phases. The study objectives are: (1) conduct a review of neighbourhood planning theories and (2) develop a prototype for downtown land use dynamics in emerging cities. The developed prototype considers physical and socioeconomics aspects. The research tools are: content analysis of real-estate reports, observation study, and preferences survey. Fereej Abdulaziz has been selected as an example. The study emphasizes the importance of policymakers in analysing the changes of neighbourhood, with an overarching aim of guiding future growth. Other Information Published in: Journal of Urban Design License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/13574809.2019.1632179